15+4x+60=11x+12

Simple and best practice solution for 15+4x+60=11x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15+4x+60=11x+12 equation:


Simplifying
15 + 4x + 60 = 11x + 12

Reorder the terms:
15 + 60 + 4x = 11x + 12

Combine like terms: 15 + 60 = 75
75 + 4x = 11x + 12

Reorder the terms:
75 + 4x = 12 + 11x

Solving
75 + 4x = 12 + 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.
75 + 4x + -11x = 12 + 11x + -11x

Combine like terms: 4x + -11x = -7x
75 + -7x = 12 + 11x + -11x

Combine like terms: 11x + -11x = 0
75 + -7x = 12 + 0
75 + -7x = 12

Add '-75' to each side of the equation.
75 + -75 + -7x = 12 + -75

Combine like terms: 75 + -75 = 0
0 + -7x = 12 + -75
-7x = 12 + -75

Combine like terms: 12 + -75 = -63
-7x = -63

Divide each side by '-7'.
x = 9

Simplifying
x = 9

See similar equations:

| 30+you=7 | | 2*(24/2y)*y=48 | | 5u(8u-1)=0 | | 4y=14-2x | | -1=-4+b | | (x^69-i^69)(x^69+i^69)=0 | | dy/dx=1/(2x-y^2) | | 7(x+2)=2x+57 | | 108=4z | | y=1/(2x-y^2) | | 0.5=1-e^-((t-1)/10) | | 4(4-a)-2(a-4)=-10-2a | | -2(5v-3)+3v=3(v+4) | | 7x+19+2x+15=133 | | -4h+6=-6h-8 | | 21b=14+b | | -17=m+71 | | 126=3p | | 1/3r-5=6 | | X*(x-5)=126 | | a+3b+5c=30000 | | 5r(r-7)=0 | | 3t-8=-7t | | 12x+1+10x=133 | | 2*x*y=48 | | 8/2H=8 | | 10-4x=11-x*3 | | 2q=-6q-8 | | 3x^3+37x-84=0 | | 10-4c=11-x*3 | | 2/3=x10 | | 1/7(-14r)= |

Equations solver categories